Principais usos de processos verbais e metáforas interpessoais em artigos de linguística aplicada - Vivan, Élide Garcia Silva (2010)
This study is part of Project DIRECT: Em direção à linguagem do trabalho (PUCSP/ LAEL), and was developed under two projects, primarily through the Project Network that aims to describe the production of scientific articles from different areas in two languages - Spanish and Portuguese, and the second and current project designed SAL (The Systemics Across Language Research Network), which analyzes the use of grammar in different languages in its context English, Japanese, Chinese, Thai, Spanish (Argentina) and Portuguese (Brazil). At this moment, in Brazil, this project focuses on studying scientific papers. This thesis analyzes the representation of the message and positioning of the author expressed in articles in the area of Applied Linguistics. In this sense, this work is based on Systemic- Functional Linguistics (SFL), especially in the writings of Halliday (1994/2004), Halliday and Hasan (1989), Eggins (1994) and Thompson (1996), Martin (2003) and Martin & Rose (2008), among others. The SFL explores the social functions of language in use, considering language as a probabilistic system in which the choices made by users of a language do not occur by chance, but according to the cultural and situational contexts. Thus, the SFL conceives language in a socialsemiotic perspective (HALLIDAY and HASAN, 1989) language as a system of meanings related to social structure. Based on such considerations, this research studies the data in context of use; watches them quantitatively, with the support of Corpus Linguistics, and analyzes them qualitatively through SFL. The corpus of the study consisted of 43 articles published from 2000 to 2007 in the Journal of Documentation Studies in Theoretical and Applied Linguistics - DELTA. The general research question is: what are the representation patterns of the message and the author´s position expressed in articles in the area of Applied Linguistics? To answer this question within the ideational metafunction, the verbal processes were analysed. The use of verbal processes is assured when authors deem necessary to bring another participant to the discourse, a voice of authority that will give their comments a greater force, increasing truth-value. Whenever used, these processes confirm, clarify and explain facts or situations, thus playing an indispensable role in support of the arguments presented by the author before the theme of his text. In the context of interpersonal metafunction, some features of the system mode related to the authors´ attitude, their commitment or modal responsibility before their text and interlocutor were analysed. In relation to verbal processes, the results show low frequency of citation, followed by projection and a high number of nominalization use, confirming the employment of elaborated language rather than hypotactic reports or paratactic citations. Interpersonal aspects revealed that the different choices and combinations of language elements, in terms of interpersonal metaphor, indicate to the reader the probability and possibility of the author´s involvement with the text, as well as his commitment toward the discussion proposed in the article